What if Output Persistence is Disregarded by an Opportunistic Incumbent? - Caleiro, António (2015)
This note presents the consequences of output persistence being disregarded by an electorally motivated incumbent. In this case, incumbent’s policies are suboptimal not only socially but also from the electoral point of view.